Estimation of the prevalence of autism spectrum disorders in Colombia based on the governmental data system. (October 2022) - García-Zambrano, Sebastián; Orozco-Barrios, Laurent G.; Jacobs, Eric
Abstract: The prevalence of Autism Spectrum Disorders (ASD) must be estimated to provide better health care services and allocate funds to specific locations for this population (Chiarotti & Venerosi, 2020). There has been no research on the prevalence of ASD in Colombia, and few data from other Latin American nations have been published (Elsabbagh, et al., 2012; Zeidan, et al., 2022). Thus, the purpose of this study is to estimate the prevalence of ASD in Colombia in 2019 and to analyze the number of persons served between 2009 and 2019. This descriptive epidemiological study uses information from the Colombian Health Department system (SISPRO) to obtain reliable data to estimate the prevalence. The International Statistical Classification of Diseases and Related Health Problems was used to find information about healthcare services provided to autistic children in the country. In Colombia, 18, 695 autistic children aged 0–14 received health services in 2019, for an estimated prevalence of 18.7/10, 000 children. The statistics revealed an increasing trend in the number of persons with ASD served between 2009 and 2019. In terms of prevalence distribution by region, the prevalence ranged from 0.23 per 10, 000 children (Guainía) to 17.29 per 10, 000 children under 14 years old (Atlántico). This is the first study to describe the significant differences in the prevalence of ASD across Colombian regions, and future research is recommended. Highlights: This is the first study in Colombia to use administrative data to compute the prevalence of ASD. The prevalence of ASD in children aged 0–14 years is increasing, rising from 4.20/10, 000 in 2009–18.73/10, 000 in 2019. The country's ASD prevalence is not evenly distributed, with most cases clustered in the Caribbean and Andean regions. This is a starting point for the development of public policies for children with ASD in Colombia.